PERSPECTIVE: EVOLUTION OF FLOWER COLOR IN THE DESERT ANNUAL LINANTHUS PARRYAE: WRIGHT REVISITED - Schemske, Douglas W; Bierzychudek, Paulette (Evolution, 2001)
Linanthus parryae, a diminutive desert annual with white or blue flowers, has been the focus of a long-standing debate among evolutionary biologists. At issue is whether the flower color polymorphism in this species is the product of random genetic drift, as Sewall Wright argued, or of natural selection, as proposed by Carl Epling and his colleagues. Our long-term studies of three polymorphic populations in the Mojave Desert demonstrate that flower color is subject to selection that varies in both time and space in its direction and magnitude. For all sites taken together, blue-flowered plants produced more seeds than white-flowered plants in years of relatively low seed production, whereas white-flowered plants had higher fitness in years of high seed production. Evidence of selection on flower color was found in two of the three study sites. Differences in fitness between the color morphs were sometimes large, with selection coefficients as high as 0.60 in some years. Our longest period of observations was at Pearblossom site 1, where plants reached appreciable densities in seven of the 11 years of study. Here we found significant differences in the seed production of the color morphs in six years, with three years of blue advantage and three years of white advantage. For all sites taken together, total spring precipitation (March and April) was positively correlated with both absolute and relative seed production of the color morphs. At Pearblossom site 1, blue-flowered plants typically had a fitness advantage in years of low spring precipitation, whereas white-flowered plants had a fitness advantage in years of high spring precipitation. This temporal variation in selection may contribute to the maintenance of the flower-color polymorphism at Pearblossom site 1, whereas gene flow from neighboring populations is proposed as the principal factor maintaining the polymorphism at the other study sites. We found no significant differences between the color morphs in pollinator visitation rate or in their carbon isotope ratio, a measure of water-use efficiency. Although the mechanism of selection remains elusive, our results refute Wright's conclusion that the flower color polymorphism in L. parryae is an example of isolation by distance, a key component of his shifting balance theory of evolution. Corresponding Editor: C. Eckert